2017
DOI: 10.1016/j.cplett.2017.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity for CO2 over CH4 on a functionalized periodic mesoporous phenylene-silica explained by transition state theory

Abstract: Periodic mesoporous organosilicas-PMO, CO 2 /CH 4 separation, Transition state theory, DFT Highlights • We study the interaction of functionalized periodic mesoporous phenylene-silica APTMS@Ph-PMO with CO 2 and CH 4 by dispersion corrected periodic density functional theory (DFT). • From a transition state theory based approach using such DFT results, an estimation of initial CO 2 /CH 4 selectivity is presented for a wide temperature range. • At ambient temperatures (298 K), such determined CO 2 /CH 4 selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…However, materials with a high CO 2 selectivity over CH 4 at standard temperature/pressure operation conditions are needed. There is exhaustive experimental research on promising materials, yet performance regretfully often remains low.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…However, materials with a high CO 2 selectivity over CH 4 at standard temperature/pressure operation conditions are needed. There is exhaustive experimental research on promising materials, yet performance regretfully often remains low.…”
mentioning
confidence: 99%
“…Materials screening is conveniently first sieved from simulations accurately estimating the interaction of a given material with CO 2 and CH 4 . Among other methods, , density functional theory (DFT) including dispersion (DFT-D) has proven especially useful to size CH 4 interactions with Ni and Co surfaces, nanoporous carbons, zeolites, periodic mesoporous phenylene-silica (PMOs), and metal–organic frameworks (MOFs) . Similar examples are available for CO 2 , and in combination with statistical thermodynamics based approaches, realistic and therefore useful estimates of selectivity and uptake rates are accessible. , …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…demonstrated that amine groups could be functionalized in the PMOs through mononitration with nitric acid in the presence of sulphuric acid, followed by the reduction with tin chloride and HCl. The amine‐functionalized samples showed higher selectivity for the adsorption of CO 2 molecules in comparison with the CH 4 molecules . The same group also manipulated the amine‐functionalized PMOs for the formation of dialkylated amine through the microwave‐assisted approach.…”
Section: Synthesis Of Organo‐functionalized Molecular Sievesmentioning
confidence: 99%